Nutrient content and uptake of field pea and baby corn intercrops as affected by weed management and planting patterns - Devi, Moirangthem Thoithoi; Singh, V.K. (Annals of Agricultural Research, 2016)
A field experiment was conducted during two consecutive seasons of rabi 2011-13 at G.B. Pant Universityof Agriculture Technology, Pantnagar to find out the effect of planting pattern and weed managementpractices on yields, and nutrient content and uptake of field pea and baby corn in field pea (Pant P-13)+ baby corn (Surya) intercropping system. The experiment was laid-out in split-plot design keepingfour planting patterns as main-plot and four weed management practices as sub plot with threereplications. Sole planting of field pea recorded significantly higher grain (2264 and 1434 kg ha-1) andstraw yields (3263 and 2540 kg ha-1) during 2011-12 and 2012-2013 than yield obtained as a componentcrop in paired planting of maize (30/60 cm) + field pea (2:2) and planting of maize + field pea (1:1).Baby corn yield was similar in sole, paired (2:2) and 1:1 planting, but significantly higher stover yieldof baby corn (3576 kg ha-1and 3533 kg ha-1, during 2011-12 and 2012-2013, respectively) was obtainedfrom sole crop than other planting methods during both years. Sole planting of either field pea orbaby corn recorded significantly higher total nitrogen, phosphorus and potassium uptake than plantingof maize + field pea (1:1) and paired planting of maize (30/60 cm) + field pea (2:2) during both theyears. Hand weeding (HW) at 30 days after sowing (DAS), pre emergence application of pendimethalin1 kg ha-1 and post emergence application of imazethapyr 50 g ha-1 (30 DAS) improved yields of fieldpea and baby corn than weedy check. Hand weeding (30 DAS) and pre-emergence application ofpendimethalin 1 kg ha-1 resulted in higher total nitrogen, phosphorus and potassium uptake by fieldpea and baby corn as compared to post emergence application of imazethapyr 50 g ha-1(30 DAS) and